[LB.01.23] BLOOD PRESSURE AND VASCULAR PHENOTYPE IN CHILDREN AND ADOLESCENTS WITH SICKLE/BETA-THALASSEMIA. (September 2017) - Stabouli, S.; Economou, M.; Printza, N.; Teli, A.; Dotis, J.; Papadopoulou, E.; Antza, C.; Kotsis, V.; Papachristou, F.; Zafeiriou, D.
Abstract : Objective: Blood pressure (BP) in patients with sickle cell disease has been reported to be lower than in the general population. Despite low BP, sickle cell disease is associated with increased risk of cardiovascular disease. The aim of the present study was to investigate the prevalence of BP phenotypes and possible differences in arterial stiffness in pediatric patients with sickle/beta thalassemia (S/b-thal) compared with matched controls. Design and method: We included in the study 16 pediatric S/b-thal patients and 16 controls matched for age and sex. Controls were otherwise healthy children and adolescents visiting our hypertension center for suspected hypertension. All patients underwent ambulatory BP monitoring and measurement of carotid-femoral pulse wave velocity (cf-PWV). Results: Mean age of the study population was 13.30 ± 4.63 years (34.4% boys). Despite lower office systolic BP levels (115.43 ± 10.03 vs. 123.37 ± 11.92 mmHg, S/b-thal vs. controls, P = 0.05), there was no statistical significant difference in 24 h, daytime and nighttime BP. Twenty five % of the S/b-thal patients and 43.8% of the controls presented office hypertension (P = NS), while 18.8% of the S/b-thal patients and 25% of the controls presented hypertension by ambulatory BP levels (P = NS). All S/b-thal patients with office hypertension presented normal ambulatory BP values (white-coat hypertension). None of the S/b-thal patients had daytime hypertension, while all 18.8% presented nighttime hypertension with office normotension < 90th percentile (masked hypertension). S/b-thal patients and controls presented equal prevalence of masked hypertension (19%). S/b-thal patients presented also similar levels of cf-PWV with controls (7.1 ± 1.25 vs. 7.25 ± 1.43 m/sec, P = NS) and an 18.8% of the patients presented cf-PWV levels above the 95th pc for age and sex. Conclusions: Children and adolescents with S/b-thal present similar prevalence of BP phenotypes and levels of cf-PWV with pediatric population referred for suspected hypertension. A significant number of children and adolescents with S/b-thal may have nighttime hypertension despite normal office BP levels.